Moderasi Dakwah di Era Digital: Tantangan dan Peluang dalam Membangun Peradaban Baru - Rini Shofiah Pohan; Elismayanti Rambe (PT. Willy Print Art, 2024)
Moderation in preaching is a view or attitude that always tries to take a middle position between two opposing and excessive attitudes so that one of the two attitudes in question does not dominate a person's thoughts and attitudes. In other words, moderation in da'wah is a da'wah attitude that gives every value or aspect that conflicts with a certain part no more than its proper portion, is non- judgmental, humanizes and glorifies humans, and lives in harmony in diversity. This research will use a qualitative approach with in the form of a literature review. Current technological developments have an influence on all fields, including the development of da'wah which has an impact on changes in society. This phenomenal change in society must be balanced with changes in the way of preaching carried out by da''i. Da'wah must not walk in place and only use conventional methods (lectures). Da'wah must be dynamic, progressive and full of innovation. The preachers need to create new creations that are more grounded and can bring benefit to the people. Da'wah needs to be packaged in a more humane, dialogical way, meeting the needs and abilities of the community. Moderation in preachingisa necessityin thisdigital era, asan effort to welcome a new civilization.